Kekerabatan Bahasa Jawa, Sunda, dan Melayu Betawi - Ramadhayani, Nanda; Widayati, Dwi; Dardanila, Dardanila (Aksara: Jurnal Bahasa dan Sastra, 2023)
By examining the percentage of kinship and the time that has passed since the three languages separated, this study seeks to investigate the relationship between Javanese, Sundanese, and Betawi Malay. The speaking and listening approach (interview), along with note-taking and recording strategies, is the method utilized to collect data. The grouping method combined with lexicostatistics and glotochronology techniques is used in data analysis. Both formal and informal methods are used to present the data analysis results. The study's findings demonstrate that the three languages are related to one another and share a protolanguage. Sundanese and Betawi Malay are related to Javanese by 94%, Javanese and Betawi Malay by 58%, and Javanese and Sundanese by 36%. In light of the study's findings, it was determined that: Sundanese and Betawi Malay have language status, whereas Javanese and Sundanese belong to the same language family, according to research findings on the linguistic relationships between Sundanese, Javanese, and Betawi Malay. As a result, it can be assumed that although Javanese and Sundanese belong to different groups, Betawi Malay and Sundanese belong to the same group. Keyword: Relationship, Javanese, Sundanese, Betawi Malay